Intensity level and on-court role of wheelchair rugby players during competition - Borel, B.; Lacroix, J.; Daviet, J. C.; Mandigout, S. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: This study aims at quantifying the level of physical activity of wheelchair rugby players during matches in order to compare defensives players (DP) and offensives players (OP) profiles. Our hypothesis is that OP would present a higher energy expenditure and intensity level values during matches than DP, due to specific actions according to the on-court role. METHODS: Fifty-two players, including 24 DP and 28 OP (mean age of 34±9 years), from eight French teams involved in the national elite championship and in the French national cup, participated. The seven wheelchair rugby players` classes were differentiated from 0.5 points (most severe deficiencies) to 3.5 points (less severe deficiencies). DP and OP were regrouped from 0.5 to 1.5 points and from 2 to 3.5 points, respectively. Energy expenditure (in kcal), intensity level (in metabolic equivalent of task) and physical activity time (in minutes) of wheelchair rugby players during competition were evaluated. RESULTS: Statistical analysis between DP and OP showed a significant difference in vigorous activity time with a higher vigorous activity time for OP than DP; P<0.007), associated with higher mean intensity level for OP vs. DP (4.3±1.0 METs vs. 3.8±0.9 METs respectively; P=0.049). No significant differences between DP and OP were found for active energy expenditure (385±158 kcal vs. 446±199 kcal, for DP and OP respectively) during matches. CONCLUSIONS: This study highlighted significantly different wheelchair rugby player profiles between competing DP and OP for the time spent in high intensity and intensity level. Offensive players were more explosive during a match than DP; therefore, training should be adapted accordingly to their roles.